PENINGKATAN KEMAMPUAN MEMBACA INTENSIF MENGGUNAKAN STRATEGI KWL SISWA KELAS III SEKOLAH DASAR - Salman, Reni Rohayu (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
this research aimed to describe improving the student intensive reading ability using KWL strategy. It was action research that used both of qualitatif and quantitative approaches. Instrument in this research were observation sheet and test. Based on the research result, it was found that using KWL strategy improved the student intensive reading ability.   Kata kunci: membaca intensif; strategi kwl; siswa SD